Researching Adult Learners’ Reading Histories and Practices. - Christine Jarvis (Adult Education Research Conference, 2000)
This paper presents the results of an empirical study which explored the reading histories and practices of mature women students on a UK Access to Higher Education course. Such courses provide an alternative route to Higher Education for adults who left school without achieving University entry qualifications. The paper considers a relatively neglected aspect of research in adult education – research into students’ reading practices. It argues that such research can enable us to support more effectively adult returners whose approaches to texts may be dramatically different from those of individuals who have experienced a conventional education.